The development of an ingestible biosensor for the characterization of gut metabolites related to major depressive disorder: hypothesis and theory - Densil, Amanda; George, Mya Elisabeth; Mahdi, Hala; Chami, Andrew; Mark, Alyssa; Luo, Chantal; Wang, Yifan; Ali, Aribah; Tang, Pengpeng; Dong, Audrey Yihui; Pao, Sin Yu; Suri, Rubani Singh; et al. (Frontiers in Systems Biology, 2023)
The diagnostic process for psychiatric conditions, such as Major Depressive Disorder (MDD), is guided by the Diagnostic and Statistical Manual of Mental Disorders (DSM) in North America. Revisions of the DSM have led to lowered diagnostic thresholds across the board, incurring increased rates of both misdiagnosis and over-diagnosis. Coupled with stigma, this ambiguity and lack of consistency exacerbates the challenges that clinicians and scientists face in the clinical assessment and research of MDD. While current efforts to characterize MDD have largely focused on qualitative approaches, the broad quantitative variations in physiological traits associated with MDD suggest the immense potential of using biomarkers to address this issue. Investigations of biomarkers related to MDD have highlighted the importance of the gut-brain axis in influencing mental health via communication between the central and enteric nervous systems. Gut inflammation, gut permeability, and dysregulated gut metabolite concentrations have been linked to dysfunctional neuronal pathways and an increased susceptibility to MDD. Specifically, the correlation between MDD and increased indole, decreased butyrate, and decreased tetrahydrofolate concentrations, is well supported. Here, we propose additional MDD gut biomarkers to include hydrogen peroxide and tetrathionate which may be found in decreased or increased concentrations respectively. The long-term goal of this study is to develop a probiotic E. coli multi-input ingestible biosensor for the characterization of key gut metabolites implicated in MDD. An ingestible biosensor enables direct surveillance of the gut lumen, providing vital information on the microbiome which stool and serum samples cannot capture. Our proposed biosensor utilizes DNA writing with CRISPR based editors for the molecular recording of signals, and riboflavin detection as a means to establish temporal and spatial specificity in the gut. We test the feasibility of this approach through prototype building of the sensors and kinetic modeling of the system. Ultimately, we hypothesize that through the characterization of key metabolites indicative of MDD in the gut, a greater understanding of disease pathophysiology, assessment, and treatment response can be achieved.